The empirical research of the relationship between internal social capital and relational psychological contract and employee' innovation behavior. Issue 4 (3rd July 2016) - Wu, Tung-Ju; Sun, Rui; Lin, Zi-Fen
Abstract: Individual innovation is the basis for the organizational innovation. Therefore, how to keep employees sustained power of innovation is an important factor for enterprises to maintain competitive advantage. After large sample survey of employees, the essay used SEM techniques to analyze the relationship between internal social capital, relational psychological contract and employees' innovation behavior. The results show that: (1) social interaction has a direct influence on employees' innovation behavior, shared vision and trust doesn't directly affect employees' innovation behavior, but they affect employees' innovation behavior through the mediation of the relational psychological contract; (2) relational psychological contract has a significant direct influence on employees' innovation behavior. These results not only support the existing research conclusion, but also have certain enlightenment significance for enterprises to maintain employees' continuous innovation.